2019
DOI: 10.2478/rtuect-2019-0097
|View full text |Cite
|
Sign up to set email alerts
|

Implementing User Behaviour on Dynamic Building Simulations for Energy Consumption

Abstract: User behaviour influences the energy consumption of domestic properties with different range of variations and this has an effect on the results of building simulations based on default or general values, as opposed to implementing user behaviour. The aim of this paper is to evaluate and quantify the effect of implementing user behaviour in building dynamic simulation to calculate heating and domestic how water energy consumption to reduce the performance gap. The results for space heating and domestic hot wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Possible future research would focus on the analysis of user behaviour in heating consumption. Jimenez-Bescos et al [30] concluded that incorporating user behaviour into building simulations, a more accurate estimation of energy consumption could be achieved.…”
Section: Annual Heating Demand and Cost Calculation Modelmentioning
confidence: 99%
“…Possible future research would focus on the analysis of user behaviour in heating consumption. Jimenez-Bescos et al [30] concluded that incorporating user behaviour into building simulations, a more accurate estimation of energy consumption could be achieved.…”
Section: Annual Heating Demand and Cost Calculation Modelmentioning
confidence: 99%
“…User behaviour has a non-negligible importance for energy consumption. Today, even building simulations aim to take user behaviour into account [2]. Interventions to change energy use behaviour have the potential to help reduce energy demand, avoid greenhouse gas emissions and reduce energy costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study focusing on the impact of user behaviour and how to incorporate user behaviour on building simulation, Jimenez-Bescos et al [22] have noticed a reduction in comfort due to future weather will generate a change in behaviour from users to adapt to higher temperatures.…”
Section: Introductionmentioning
confidence: 99%